Lumbar Fusion for Degenerative Disease: A Systematic Review and Meta‐Analysis. Issue 5 (May 2017) - Yavin, Daniel; Casha, Steven; Wiebe, Samuel; Feasby, Thomas E; Clark, Callie; Isaacs, Albert; Holroyd‐Leduc, Jayna; Hurlbert, John R.; Quan, Hude; Nataraj, Andrew; Sutherland, Garnette R.; Jette, Nathalie
Abstract : BACKGROUND: : Due to uncertain evidence, lumbar fusion for degenerative indications is associated with the greatest measured practice variation of any surgical procedure. OBJECTIVE: : To summarize the current evidence on the comparative safety and efficacy of lumbar fusion, decompression‐alone, or nonoperative care for degenerative indications. METHODS: : A systematic review was conducted using PubMed, MEDLINE, EMBASE, and the Cochrane Central Register of Controlled Trials (up to June 30, 2016). Comparative studies reporting validated measures of safety or efficacy were included. Treatment effects were calculated through DerSimonian and Laird random effects models. RESULTS: : The literature search yielded 65 studies (19 randomized controlled trials, 16 prospective cohort studies, 15 retrospective cohort studies, and 15 registries) enrolling a total of 302 620 patients. Disability, pain, and patient satisfaction following fusion, decompression‐alone, or nonoperative care were dependent on surgical indications and study methodology. Relative to decompression‐alone, the risk of reoperation following fusion was increased for spinal stenosis (relative risk [RR] 1.17, 95% confidence interval [CI] 1.06‐1.28) and decreased for spondylolisthesis (RR 0.75, 95% CI 0.68‐0.83). Among patients with spinal stenosis, complications were more frequent following fusion (RR 1.87, 95% CI 1.18‐2.96). Mortality was not significantly associated with any treatment modality. CONCLUSION: : Positive clinical change was greatest in patients undergoing fusion for spondylolisthesis while complications and the risk of reoperation limited the benefit of fusion for spinal stenosis. The relative safety and efficacy of fusion for chronic low back pain suggests careful patient selection is required (PROSPERO International Prospective Register of Systematic Reviews number, CRD42015020153).